The impact of small arms on children and adolescents in Central America and the Caribbean : a case study of El Salvador, Guatemala, Jamaica and Trinidad and Tobago - Alvarez, Daniel Luz i (Unicef Panama CityPA, 2007)
Uncovers the evidence and analyzes the impact of armed violence and small arms proliferation on the lives of boys and girls in four Central American and Caribbean countries.